Comparative Study of the Adsorption Effects of Activated Carbons from Coconut Shell and Groundnut Shell as Absorbents for Metal Ions - K.E, Ochiagha; N.C, Eboagu,; U.G, Eze,; C.C, Odidika,; C. C. , Aralu (European Journal of Applied Sciences, 2022)
The main objective of this research was to compare the effect of contact time, concentration, and temperature in preparing activated carbon from coconut shells and groundnut shells. The research was carried out at a temperature range of 35 -65 and the maximum adsorption capacities for Pb(II) and Cd(II) ions were respectively 3.61 and 3.34 mg/g for coconut shell, 3.21 and 3.13 mg/g for groundnut shell at the optimum temperature of 35 . Thus the maximum ion adsorption capacities followed the trend: coconut shell>groundnut shell. These results were obtained using the following optimum conditions: initial metal ions concentration of 100 mg/dm3, adsorbents weight of 0.5g, time of 30 min, and pH of 6. The adsorption of the metal ions by the adsorbents was found to decrease with an increase in the initial concentration of the metal ions in an aqueous solution. Also, the adsorption rate increased with temperature. The result of the work revealed that activated carbons derived from coconut shells and groundnut shells can be used as a low-cost alternative to commercial adsorbents in the removal of Pb(II) and Cd(II) ions from water and wastewater.